Ethical Leadership and Administrative Competence: A Study of Ethiope East and Ethiope West Local Government Areas of Delta State, Nigeria - Gbosien Chris, SOKOH (International Journal of Psychosocial Rehabilitation, 2024)
Unethical and administrative corrupt practices have emerged as part of the criticisms leveled against local governments in Nigeria. Perhaps, the problem of employees’ apathy and lack of effort to perform the core functions of a modern state is not simply a matter of laziness; rather, there are often healthy reactions by normal people to an unhealthy environment created by unethical leadership. This underscores the importance of ethical leadership in influencing administrative competence. It is against this backdrop that this study examines the relationship between ethical leadership and administrative competence in Ethiope Easst and Ethiope West Local Government Areas of Delta State, Nigeria. A cross-sectional survey research design was adopted and data was collected via a survey of 177 respondents randomly selected from a population of 317 employees of the Ethiope East and Ethiope West Local Governments. Data collected were analyzed using correlation and linear regression analysis with the aid of Statistical Package for Social Science (SPSS) version 23. The results of the study revealed that there is a significant relationship between ethical leadership and administrative competence of employees. The study also showed that ethical leadership exerts a positive and statistically significant effect on administrative competence in Ethiope East and Ethiope West Local Government Areas of Delta State, Nigeria. Based on these findings, the study concludes that ethical leadership has significant influence on administrative competence. The study therefore recommendes among others that local government leadership should rewards ethical conduct and discipline unethical conduct by exhibiting ethical behaviour that promote administrative competent.